2018
DOI: 10.3389/fnbeh.2018.00227
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Dependent Effects of Environmental Enrichment on Spatial Memory and Brain-Derived Neurotrophic Factor (BDNF) Signaling in a Developmental “Two-Hit” Mouse Model Combining BDNF Haploinsufficiency and Chronic Glucocorticoid Stimulation

Abstract: Neurodevelopmental disorders are thought to be caused by a combination of adverse genetic and environmental insults. The “two-hit” hypothesis suggests that an early first “hit” primes the developing brain to be vulnerable to a second “hit” during adolescence which triggers behavioral dysfunction. We have previously modeled this scenario in mice and found that the combined effect of a genetic hapolinsuffuciency in the brain-derived neurotrophic factor (BDNF) gene (1st hit) and chronic corticosterone (CORT) trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…All these different factors (e.g., strain, sex, etc. ; [ 55 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ]) could thus distinctly influence the outcome of the ( S )-MK-26 pharmacological treatment. Indeed, several reports have described that brain physiological processes and dopamine-associated neuropathological maladies are differentially manifested depending on the sex of the patient [ 176 , 177 , 178 , 179 ], as is the case for Parkinson’s disease, which manifests predominantly in aged men.…”
Section: Limitationsmentioning
confidence: 99%
“…All these different factors (e.g., strain, sex, etc. ; [ 55 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ]) could thus distinctly influence the outcome of the ( S )-MK-26 pharmacological treatment. Indeed, several reports have described that brain physiological processes and dopamine-associated neuropathological maladies are differentially manifested depending on the sex of the patient [ 176 , 177 , 178 , 179 ], as is the case for Parkinson’s disease, which manifests predominantly in aged men.…”
Section: Limitationsmentioning
confidence: 99%
“…A recent study also found EE to differentially activate neural circuits in FVB/N mice, promoting social interactions in female mice but aggressive behaviors in male mice [ 242 ]. Additionally, many studies have also noted the sex-dependent effects of EE in their respective investigations [ 243 , 244 ].…”
Section: Discussion and Limitations Of Current Studiesmentioning
confidence: 99%
“…In another “two-hit” model of perinatal neuroimmune activation, two weeks of EE in late adolescence was shown to increase BDNF expression, TrkB expression, upregulate the expression of several excitatory-related receptors (NMDA, GluNR1, 2A and 2B) in “two-hit” mice compared to controls. Moreover, this was correlated with improved spatial working memory performance [ 115 ]. Additionally, Zajac et al found that two weeks of voluntary exercise and EE in late adolescence had unique effects on serotonergic receptor expression in a transgenic mouse model of Huntington’s Disease.…”
Section: Types Of Plasticity-evoking Stimulationsmentioning
confidence: 99%